2013
DOI: 10.5897/ajar12.1802
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the morphological and molecular diversity in Amaranthus spp.

Abstract: Genetic diversity and relationships of 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is the individual parameter which shows the capacity of the plant to produce. Kumari Anjali et al [15] found similar results for seed yield per plant in different grain amaranthus varieties.…”
Section: Seed Yield/plant (G)mentioning
confidence: 68%
“…It is the individual parameter which shows the capacity of the plant to produce. Kumari Anjali et al [15] found similar results for seed yield per plant in different grain amaranthus varieties.…”
Section: Seed Yield/plant (G)mentioning
confidence: 68%
“…Cluster 1A included AVKATN and AVNEK while cluster 1B included AVTHK and AVKOK. Previously 28 have assessed the molecular diversity in Amaranthus spp. 29 had reported genetic relationship among 8 Amaranthus palmeri inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…(L.)] belongs to the family amaranthaceae and genus Amaranthus. The word "Amaranthus" has derived from Greek language which means "one that does not wither" or "never fading" [3]. The genus Amaranthus consists of a large number of species that differ in morphology, yield and also nutrient status.…”
Section: Introductionmentioning
confidence: 99%